Effective Maternal Care Application Increases Knowledge of Intranatal Standard Operating Procedures - Wieda Widyatry Qarragita; Yayat Suryati; Juju Juhaeriah; Ida Maryati; Murtiningsih Murtiningsih (Postgraduate, University of Mataram, 2023)
Not optimal information system facilities have become one of the obstacles in the learning process so that in some courses the failure rate is still high, one of which is maternity nursing so that effective and interesting learning media is needed, one of which is the Maternal Care Application. The purpose of this study was to determine the effectiveness of the Maternal Care Application in increasing knowledge of Intranatal Standard Operating Procedures (SPO) in Undergraduate Nursing Students. The type of research used is quantitative experimental in nature, using quasi-experimental rankings, with the form of pre-test and post-test with control group design, with the experimental group using applications and controls using power point. The population in this study was 144 active students in the second semester of the Bachelor of Nursing Study Program using simple random sampling of 60 students. Normalized gain test (N-Gain) is used to determine the score of knowledge before and after treatment. The results showed that the application of Maternal Care was quite effective in increasing knowledge of intranatal SPO with a gain score of 0.588. In this application the researcher presents material and videos about SPO at any time with the hope that it will make it easier for students to memorize so that student knowledge increases